Interview with Robert Kates, Pathfinder in Sustainability Science - McGreavy, Bridie; Kates, Robert (Maine Policy Review, 2012)
In this interview, Robert Kates discusses the challenges of sustainability science in moving from what scientists know to actions that can provide solutions to pressing environmental and development problems. Kates notes that sustainability science has the dual mission of addressing core scientific and intellectual questions, while at the same time addressing development in particular places. He suggests that one of the key questions is how to address long-term trends and transition to a “better synthesis between environment and society.”